2015
DOI: 10.1007/s12161-015-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Fructans Content and Barley Malt Quality

Abstract: Fructans are fructose polymers derived from sucrose and like starch are naturally present in many plants as reserve carbohydrates. The aims of this study were to determine the content of fructans in both grain and malt barley samples and to examine the relationships between fructan content and malt quality parameters such as hot water extract (HWE), apparent attenuation limit (AAL) and viscosity. The relationships between fructan content and malt quality parameters were first investigated using Pearson correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Cozzolino et al. [ 22 ] and Zhou and Mendham [ 23 ] used 0.1 m AgNO 3 to inhibit enzyme activity in barley flour and malt and obtained higher peak viscosity, supporting our findings. Huang and Lai [ 21 ] used 0.0025 m AgNO 3 to inactivate α‐amylase activity in rice flour during gelatinization, while Ding et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cozzolino et al. [ 22 ] and Zhou and Mendham [ 23 ] used 0.1 m AgNO 3 to inhibit enzyme activity in barley flour and malt and obtained higher peak viscosity, supporting our findings. Huang and Lai [ 21 ] used 0.0025 m AgNO 3 to inactivate α‐amylase activity in rice flour during gelatinization, while Ding et al.…”
Section: Discussionsupporting
confidence: 90%
“…The results suggested that using 1% AgNO 3 would inhibit α‐amylase activity in rice flour with high AC and more accurately assess pasting properties. [ 22–24 ] Other studies support an increase in PV using AgNO 3 solution, but the concentration used was too low to fully inhibit α‐amylase activity during gelatinization of rice flour with higher AC. [ 19–21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, for each approach, the state of knowledge of the principle, the challenges, the current application on the market, and potential associated patents are shown. c Apparent impact of sprouting contradicts different reports (Cozzolino et al, 2016;Ispiryan et al, 2021b;Krahl et al, 2008;MacWilliam et al, 1956)…”
Section: Strategies To Produce Low Fodmap Products and Their Current ...mentioning
confidence: 77%
“…Proving these hypotheses will require the comparative evaluation of physicochemical properties of neoseries-inulin-and graminantype fructans in the future. Indeed, several studies have provided strong evidence for a positive relationship between enhanced fructan concentrations with better malting characteristics in barley varieties (Smith et al, 1980;Cozzolino et al, 2016 and references therein)…”
Section: Developmental and Tissue Specific Nature Of Barley Fructan Biosynthesismentioning
confidence: 99%